2015
DOI: 10.1177/0022002715600761
|View full text |Cite
|
Sign up to set email alerts
|

The Role of External Support in Civil War Termination

Abstract: Many studies highlight the role that international intervention can play in prolonging civil wars. Yet, direct military intervention is just one way that external actors become involved in civil conflicts. In this article, a model is developed and analyzed that shows that when the government is unsure about how external support to the rebels will help rebel war-making capacity, it is the government that will continue fighting rather than settle the dispute. Different types of external support to rebels influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 51 publications
3
60
0
1
Order By: Relevance
“…Furthermore, given the prevalence of ripeness theory, it is worthwhile evaluating if this is the most suitable framework in trying to understand civil war negotiations. The article also adds to the expanding research on the effects of external support on conflict processeswhich so far has been mostly concerned with conflict duration 19 or termination 20 while overlooking central conflict dynamics such as the initiation of talks.…”
mentioning
confidence: 99%
“…Furthermore, given the prevalence of ripeness theory, it is worthwhile evaluating if this is the most suitable framework in trying to understand civil war negotiations. The article also adds to the expanding research on the effects of external support on conflict processeswhich so far has been mostly concerned with conflict duration 19 or termination 20 while overlooking central conflict dynamics such as the initiation of talks.…”
mentioning
confidence: 99%
“…However, neither of these studies differentiated external military support by content. The only other study to have made such a differentiation and use econometric techniques to demonstrate the utility of such a differentiation, Sawyer et al (2015), is discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…However, there has been one major attempt at looking at support types with the UCDP External Support data. Sawyer et al (2015) argue that more fungible forms of support create uncertainty and prolong conflict by making settlements less attractive. Specifically, they argue that monetary funding and weaponry are the most fungible forms of support, and show that provision of these forms of support are associated with a decreased probability of conflict termination at a given point in time.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These arguments about the likely impact of intervention on domestic con ‡ict have been developed mostly in the context of incomplete information environments and bargaining games. It has been shown that civil war can be prolonged as a result of uncertainty about the extent or likelihood of external intervention (Sawyer et al, 2015;Powell 2017); and that interventions that help establish power parity among domestic actors can make con ‡ict outbreaks more likely as they create uncertainty over the con…ct outcome (Bas and Schub 2016). The expectation of intervention on the side of rebels could escalate con ‡icts as rebel demands get progressively more expansive (Jenne 2004); by making the government take preemptive action (Poast 2015); or otherwise create bargaining failures (Grigoryan 2010, Cetinyan 2003.…”
Section: Identity Intervention and The Onset Of Warmentioning
confidence: 99%